A new pathway for neuroprotection against tau hyperphosphorylation via δ-opioid receptor initiated inhibition of CDK5 and AMPK signaling - Li, Jiahui; Xu, Yuan; Balboni, Gianfranco; Xia, Ying (Frontiers in Aging Neuroscience, 2025)
IntroductionAlzheimer’s disease (AD) is a progressive neurodegenerative disease characterized by decreased memory and cognitive impairment. Abnormal tau hyperphosphorylation ultimately forms neurofibrillary tangles, which is one of the most important pathological features of AD. Since we have previously shown that the δ-opioid receptor (DOR) is neuroprotective in the brain, we asked if DOR plays any role in the control of tauopathy.MethodsIn the PC12 cell model with okadaic acid-induced tau hyperphosphorylation, cell viability and cytotoxicity were evaluated by using CCK8 assay kit and lactate dehydrogenase cytotoxicity assay kit. The techniques of western blot and immunofluorescence were used to investigate the effect of DOR on tau hyperphosphorylation.ResultsWe found that DOR activation inhibited okadaic acid-induced tau hyperphosphorylation in PC12 cells and attenuated the cell cycle reactivation and apoptosis. The DOR effect was blocked by Naltrindole, a DOR antagonist. Furthermore, the mechanistic studies showed that the DOR displayed its effect by reducing the expression of cyclin-dependent kinase (CDK) 5 and AMP-activated protein kinase (AMPK) in the model of tauopathy.DiscussionOur novel findings suggest that DOR signaling may protect neurons from AD injury by inhibiting tau hyperphosphorylation.